2018
DOI: 10.1108/sasbe-10-2018-0054
|View full text |Cite
|
Sign up to set email alerts
|

Ranking the regenerative architecture indicators for assessment of research-educational building projects in Tehran, Iran

Abstract: Purpose The purpose of this paper is to propose a hierarchically structured system of regenerative architecture indicators for assessing research-educational building projects. Design/methodology/approach First, based on a literature review of the historical roots of regenerative design and related approaches and the interviews held with experts of the related field, the paper proposes a structured framework of architectural indicators suitable for the context of Tehran. Later, the importance of criteria is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…It addresses issues such as utilizing local facilities, water and energy efficiency, waste management, environmental pollution reduction, and many other issues that deal with the methods of reaching maximum output through minimum input or concern short term returns and long term benefits. Considering all the scattered factors about economic sustainability, it has been recognized that they can be all categorized into three main principles: Efficiency, Flexibility and Strength (Armaghan and Gorji-Mahlabani, 2009;Otegbulu, 2011;Bonyad et al, 2018):…”
Section: Economic Sustainabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…It addresses issues such as utilizing local facilities, water and energy efficiency, waste management, environmental pollution reduction, and many other issues that deal with the methods of reaching maximum output through minimum input or concern short term returns and long term benefits. Considering all the scattered factors about economic sustainability, it has been recognized that they can be all categorized into three main principles: Efficiency, Flexibility and Strength (Armaghan and Gorji-Mahlabani, 2009;Otegbulu, 2011;Bonyad et al, 2018):…”
Section: Economic Sustainabilitymentioning
confidence: 99%
“…It addresses issues such as utilizing local facilities, water and energy efficiency, waste management, environmental pollution reduction, and many other issues that deal with the methods of reaching maximum output through minimum input or concern short term returns and long term benefits. Considering all the scattered factors about economic sustainability, it has been recognized that they can be all categorized into three main principles: Efficiency, Flexibility and Strength (Armaghan and Gorji-Mahlabani, 2009; Otegbulu, 2011; Bonyad et al , 2018): Efficiency: Efficiency means the most desirable degree of exploitation regarding the available resources or personal and social life management based on the existing facilities that lead to saving resources and thus, reducing ultimate costs. In fact, this feature tries to demonstrate all the practical efforts made to obtain maximum efficiency for users indicating the consequences of controlling the waste of money.…”
Section: Economic Sustainabilitymentioning
confidence: 99%
“…Also, health, hygiene, cleanliness, basic facilities and safety with respect to the construction worker's dwelling place are major aspects in protecting the social well-being of the workers. This aspect adds up to the social sustainable performance of any building during its construction stage (Bonyad et al, 2018;Sharma, 2018). Survey results indicated that 94% of the participants have considered construction workers' health and safety as an important factor to be incorporated into the assessment model.…”
Section: Assessment Indicators Of Building Performance Score Modelmentioning
confidence: 99%
“…energy annually, thereby becoming a major contributor to greenhouse gas (GHG) emissions (Sovacool and Brown, 2010;Bonyad et al, 2018). The building sector of India alone is responsible for 15%-18% of comprehensive CO 2 emission and about 30% of sulfur dioxide emissions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation